2008
DOI: 10.1139/x08-040
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between drought and shade on growth and physiological traits in two Populus cathayana populations

Abstract: Abstract:The morphological and physiological responses of two contrasting Populus cathayana Rehd. populations to three light regimes, full sunlight (control), 33% full sunlight (moderate shade), and 12% full sunlight (severe shade), were investigated under well-watered and drought conditions. The populations were from Hanyuan (relatively more annual rainfall and less annual solar radiation) and Ledu (less annual rainfall and more annual solar radiation) in western China. In both populations, drought-treated pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…Drought-induced increases in chlorophyll contents were detected here and also in previous studies (Huang et al, 2008). In addition, we found that exogenous ABA application did not affect the chlorophyll content, but there were differences in chla/b in response to drought at both light levels.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Drought-induced increases in chlorophyll contents were detected here and also in previous studies (Huang et al, 2008). In addition, we found that exogenous ABA application did not affect the chlorophyll content, but there were differences in chla/b in response to drought at both light levels.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, ␦ 13 C induced by drought, exogenous ABA application and the D + ABA treatment under SL was lower than that under FL, which suggests that the water use efficiency of seedlings is more sensitive to drought, ABA application and the combination of drought and ABA under FL. It may be that shade aids plants to maintain a higher tissue water content that mitigates drought stress (Huang et al, 2008). In addition, plant hormones play critical roles in regulating plant responses to stressful environments .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations